Psychometric Properties of the 42-Item Version of Ryff’s Psychological Well-Being Scale among Working Women in Malaysia - Nur Salimah Alias; Intan Hashimah Mohd Hashim; Mohd Haizzan Yahaya (Journal of Human Development and Communication (JoHDeC), 2025)
The purpose of this study was to explore factor structure of Ryff’s Psychological Well-being Scale. The scale was administered to 500 women employees from Malaysia’s public universities. The 42-items of Psychological Well-being scale with six subscales namely: Self-acceptance, Environmental mastery, Positive relations with others, Autonomy, Personal growth, and Purpose in life. Results from principal factor analysis with Promax rotation with scree plot extracted 4 factors which contributed 53.70 per cent cumulative variance and produced loading between 0.346 to 0.924. However, the 4-factor produced in the analysis did not stand in any factors proposed by Ryff’s, thus it yield new unidentified 4 factors. Further analysis was recommended to confirm the psychometric properties from the study.